Dual Regulation of Voltage-Sensitive Ion Channels by PIP2 - Rodríguez Menchaca, Aldo A.; Adney, Scott K.; Zhou, Lei; Logothetis, Diomedes E. (Frontiers in Pharmacology, 2012)
Over the past 16 years, there has been an impressive number of ion channels shown to be sensitive to the major phosphoinositide in the plasma membrane, phosphatidilinositol 4,5-bisphosphate (PIP2). Among them are voltage-gated channels, which are crucial for both neuronal and cardiac excitability. Voltage-gated calcium (Cav) channels were shown to be regulated bidirectionally by PIP2. On one hand, PIP2 stabilized their activity by reducing current rundown but on the other hand it produced a voltage-dependent inhibition by shifting the activation curve to more positive voltages. For voltage-gated potassium (Kv) channels PIP2 was first shown to prevent N-type inactivation. Careful examination of the effects of PIP2 on the activation mechanism of Kv1.2 has shown a similar bidirectional regulation as in the Cav channels. The two effects could be distinguished kinetically, in terms of their sensitivities to PIP2 and by distinct molecular determinants. The rightward shift of the Kv1.2 voltage dependence implicated basic residues in the S4-S5 linker and was consistent with stabilization of the inactive state of the voltage sensor. A third type of a voltage-gated ion channel modulated by PIP2 is the hyperpolarization-activated cyclic nucleotide-gated (HCN) channel. PIP2 has been shown to enhance the opening of HCN channels by shifting their voltage-dependent activation toward depolarized potentials. The sea urchin HCN channel, SpIH, showed again a PIP2-mediated bidirectional effect but in reverse order than the depolarization-activated Cav and Kv channels: a voltage-dependent potentiation, like the mammalian HCN channels, but also an inhibition of the cGMP-induced current activation. Just like the Kv1.2 channels, distinct molecular determinants underlied the PIP2 dual effects on SpIH channels. The dual regulation of these very different ion channels, all of which are voltage dependent, points to conserved mechanisms of regulation of these channels by PIP2.